Modernization of the Tax System of Uzbekistan: Tasks, Achievements and Prospects (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article examines the key aspects of modernization of the tax system of Uzbekistan in the context of globalization and digitalization of the economy. It analyzes the main directions of reforms, including reducing the tax burden, simplifying tax administration and introducing digital technologies. Highlights the problems associated with the lack of experience of state bodies and the low level of tax culture among the population. adaptation of international experience to national conditions. The article emphasizes the need for a comprehensive approach to reforming the tax system to ensure sustainable economic growth and increase the investment attractiveness of the country.